Synchronization of the unified chaotic system and application in secure communication - Grzybowski, J.M.V.; Rafikov, M.; Balthazar, J.M. (Communications in nonlinear science & numerical simulation, 2009)
This paper studies the synchronization of the unified chaotic system via optimal linear feedback control and the potential use of chaos in cryptography, through the presentation of a chaos-based algorithm for encryption.